Asking the right questions: interrogating the logic and assumptions of paradigms used to investigate interactions between procedural and declarative memory in category learning - Priya B. Kalra (Frontiers in Cognition)
In this mini-review, the methods used to investigate interactions between procedural and declarative systems in category learning are considered. Methods that were originally used to establish dissociations between memory systems may be biased toward demonstrating competition between them. In contrast, a modification of Jacoby's Process Dissociation Procedure allows researchers to consider the relative contributions of multiple processes involved in task completion. The original PDP was designed to consider the contributions of recall and familiarity to recognition, but the logic of the PDP can be applied to the contributions of procedural and declarative processes in category learning. Suggestions for improving the possibility of detecting cooperation between systems using the PDP are given.